E-Encyclopedia of Mathematics Based on Android For Class VIII Junior High School - Ririn Dwi Agustin (Department of Mathematics Education University of Muhammadiyah Malang, 2020)
Mathematics is a broad science in life. Therefore learning media innovation must be done. The purpose of this research is to create applications that can expand knowledge and skills by attracting and flexible with android based systems for grade VIII students of junior high school. Android is an operating system that is Open Source which gives freedom for developers to develop an application, with the advantages of the Android operating system, will help Android-based users to be able to joyfull a variety of applications, one of the applications is e-encyclopedia. The stages of the research carried out refer to the ADDIE development model including Analysis, Design, Development, Implementation, and Evaluation. The stages of the research that have been carried out are the Stages of research that have been carried out are goal analysis (goal analysis, analysis of learning tools and materials, analysis of ability levels and characteristics of target users), design (application design to be presented, preparation of materials, preparation of material delivery flow in the form of flowcharts, making flowcart, and approve materials needed in encyclopedia development), development (application development), implementation (computer expert approval, material experts, and field discussions and conducting limited trials), and evaluations (evaluation of applications developed, carried out for forty before).. The subjects involved grade VIII students were 10 female students and 12 male students as respondents. Feasibility test results were obtained 95% for media experts, 90% for material experts, 80% for field practitioners, and 83% for target users.